2008
DOI: 10.1186/1471-2334-8-61
|View full text |Cite
|
Sign up to set email alerts
|

Non-travel related Hepatitis E virus genotype 3 infections in the Netherlands; A case series 2004 – 2006

Abstract: Background: Human hepatitis E virus (HEV) infections are considered an emerging disease in industrialized countries. In the Netherlands, Hepatitis E virus (HEV) infections have been associated with travel to high-endemic countries. Non-travel related HEV of genotype 3 has been diagnosed occasionally since 2000. A high homology of HEV from humans and pigs suggests zoonotic transmission but direct molecular and epidemiological links have yet to be established. We conducted a descriptive case series to generate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
102
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 33 publications
11
102
1
1
Order By: Relevance
“…[59][60][61][62] In contrast to disease seen in highly-endemic areas, the patients with hepatitis E in low-endemicity areas are generally elderly, and often have other coexisting diseases, including diabetes, cardiovascular disease and prior liver disease. 63 In a series from the UK, the disease showed seasonal peaks in spring and summer and no cases during winter.…”
Section: Characteristics Of Affected Subjectsmentioning
confidence: 99%
“…[59][60][61][62] In contrast to disease seen in highly-endemic areas, the patients with hepatitis E in low-endemicity areas are generally elderly, and often have other coexisting diseases, including diabetes, cardiovascular disease and prior liver disease. 63 In a series from the UK, the disease showed seasonal peaks in spring and summer and no cases during winter.…”
Section: Characteristics Of Affected Subjectsmentioning
confidence: 99%
“…Unpasteurized milk was associated with HEV infection in an EL2 seroepidemiological study [92]. In a risk factor EL2 analysis using a structured questionnaire, dried sausages and uncooked shellfish (mussels, oysters, or both) were considered risk factors associated with cases in The Netherlands and France, respectively, but these studies did not use controls [19,51]. In the EL3 case-control study in Germany, Wichmann et al found that eating any offal or wild boar was independently associated with autochthonous HEV infection [52].…”
Section: Potential For Foodborne Zoonotic Transmissionmentioning
confidence: 99%
“…During EL2 enhanced surveillance in The Netherlands, HEV RNA was found in a water sample taken from outside a patient's home and it had an identical sequence to that of the patient but it was thought more likely that the patient contaminated the water [19]. An EL2 risk factor study conducted in France found that 15 cases (32 %) drank from their own water supply (spring or well) [51] and 1/35 samples taken from the spring was positive for HEV RNA.…”
Section: Potential For Water-borne Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, ≈10 cases/year of non-travel-related HEV infections have been diagnosed (17,18). In 2004-2006, a descriptive case study was performed to generate hypotheses about possible risk factors and transmission routes for non-travel-related HEV infections in the Netherlands (19). However, no conclusive evidence for a specifi c transmission route was observed.…”
mentioning
confidence: 99%